EFFECT OF PALIMPSEST IN THE NOVEL LE VILLAGE DE L’ALLEMAND OU LE JOURNAL DES FRERES SCHILLER BY BOUALEM SANSAL - Boudaa, Samia (PALIMPSEST / ПАЛИМПСЕСТ, 2019)
In this study, we attempt to describe and dismantle the writing mechanism in the novel Le Village de l’Allemand ou Le Journal des frères Schiller of Boualem Sansal where we detect a palimpsest effect. This process seems to be at the origin of the writing of the double in this novelistic text. Our goal here is to show how the writing in this corpus works to produce a polyphonic discourse that is pronounced through the three texts of these protagonists.